COBIT benchmarking of system development governance for a government agency in Malaysia - Hamid Z.A.; Sulaiman H. (Asian Research Publishing Network, 2023)
The lack of initiative of in-house system development governance has resulted to several issues in the working procedures of the Public Service Department of Malaysia (PSD) and mutual understanding among Business and IT People. The understanding of stakeholders, especially Business-IT people, plays an important role and is responsible for carrying out inter-related values for the success of any developed Information Systems (IS) applications. The lack of understanding on the importance to achieve PSDs business goals by IT people and failure to have applications finished on time, may lead to another enhancement or rectification of the application that causes further time and resource consumption. Likewise, the Business peoples assumption of IS development also lacks understanding on the technical complexities. The impact of improper management of in-house development process may hinder critical application deadline, systems malfunctioning, unsatisfied users and further damage to PSDs quality reputation. The COBIT benchmarking results of system development governance for a Malaysian government agency is presented in this paper through a survey. The survey was carried out among the staff members of the PSD who are internally involved with the system development process. Three (3) sets of questionnaires were distributed to the targeted group of 10 business personnel, 10 IT management personnel and 10 IT technical personnel. The set of questions were derived from COBIT 4.1 Process aturity Assessment Tool, which was developed by ISACA. It is a simple diagnostic tool based on the COBIT maturity model as defined in COBIT 4.1. The tool can be used to drive awareness and obtain buy-in with regard to the need to address IT governance. Results obtained from the tool can provide an effective and efficient way to determine IT process improvement opportunities to focus on future prioritisation mechanism based on PSDs business and IT goals, as well as the identification of important input for strategic and tactical action plans. The results indicate the alignment of business goals to IT goals, as determined by the responses obtained from PSDs staff. Additionally, the tool highlights that PSD only involved 25 IT processes out of the overall 34 COBIT IT processes. A spider-web chart illustrates the current maturity assessment result of each IT-related process in PSD. Results will provide a benchmark for PSD to evaluate their current maturity level of IT processes and the necessary strategies that can be taken to improve the maturity level of each IT processes involved in the organisation, based on their strategic goals and organisational needs. 2005 - 2016 JATIT & LLS. All rights reserved.